Learning Reproductive System Material through Think-Read-Group-Share-Reflect (TRGSR) Strategy Using Nearpod to Improve Students' Scientific Argumentation Skills - Rifaliansyah, Nanda; Sa'adah, Sumiyati; Yusup, Iwan Ridwan (FKIP - Universitas Riau, 2025)
Scientific argumentation skills are one of the supporting factors in developing students who have 21st century skills. This study aims to see the use of the TRGSR strategy using Nearpod in reproductive system learning to improve students' scientific argumentation skills. The research method used is Quasi-experimental with Non-equivalent Control Group Design. The sample used in this study were two classes, the experimental class and the control class with a total of 72 students using the Purposive Sampling method. There are three instruments used to measure the improvement of scientific argumentation skills, namely the implementation observation sheet, student response questionnaire, and scientific argumentation skill level test. The results of the study from the implementation of teacher and student activities in the experimental class were 87% (Very Good). The student response to reproductive system learning in the experimental class was 75.42% (Good). The improvement of scientific argumentation skills in the experimental class was classified as High with an N-Gain value of 0.72 while the control class was 0.62 (Medium). Meanwhile, there was an increase in each level of scientific argumentation skills in the experimental class with a final average Post-test of 81.67 (Excellent).